Atrial Thrombus in a Neonate: A Diagnostic Challenge - Sheen, Alicia; De Oliveira, Elizabeth R.; Kim, Richard W.; Parham, David; Lakshmanan, Ashwini (American Journal of Perinatology Reports, 2015)
Introduction Left atrial thrombus is a rare finding in a neonate. In the previous literature, atrial thrombi have been associated with catheter placement or congenital heart disease in a preterm infant.Case We report the case of a full-term neonate with no known risk factors found to have a left atrial thrombus. The neonate was born at 38 weeks' gestation to a 31-year-old female via cesarean section who was sent to the normal nursery. On postnatal day 5, the infant was noted to have low-to-medium level of oxygen saturations (∼90%) and was transferred to the neonatal intensive care unit with an echocardiogram completed on postnatal day 6 demonstrating a mobile, pedunculated mass attached to the left atrial septum with an appearance concerning for atrial myxoma. The infant underwent surgical resection on postnatal day 8 and pathology revealed the mass to be a left atrial thrombus.Discussion The rare finding of an atrial thrombus in a neonate has previously been associated with central venous catheter placement or congenital heart disease. This case is unusual in that the patient had neither condition. Although echocardiogram findings appeared more consistent with atrial myxoma, final pathology revealed a left atrial thrombus. Additionally, hypercoagulability work-up for this neonate was largely negative. This report underscores the importance of identification, search for etiology, and prompt therapy to prevent potential catastrophic outcomes.
Keywords: atrial thrombus; neonate; infant; thrombus resection; heparin